The possibility of the nuclear magnetic resonance methods using for reference standards certification - N. E. Kuzmina; S. V. Moiseev; V. A. Yashkir; E. V. Osintseva (Стандартные образцы)
The article describes the uncertainty sources for the main stages of quantitative measurements by NMR method. It is shown that the NMR method is effective for measuring of the components molar ratio, the components relative weight portion and the components absolute content during the reference standards certification.